2011
DOI: 10.5897/ajb11.1069
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of volatile components of flower, leaf, peel and juice of Page mandarin [(Citrus reticulata var Dancy Citrus paradisi var Duncan) Citrus clementina]

Abstract: The volatile flavor components of flower, leaf, peel and juice of 'Page' mandarin were investigated in this study. Flower components were extracted by using ultrasound (US) water bath apparatus and then eluted by n-pentane : diethylether (1:2) solvent. Leaf flavor components were extracted by using water distillation method and then eluted by using n-hexane solvent. Juice flavor components were extracted by using poly dimethyl siloxane membranes (PDMS) and then eluted by pentane : dichloromethane (2:1). Peel f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…In fact, medium polarity solvents (diethyl ether, dichloromethane or ethyl acetate) extract more polar and higher MW compounds such as hexadecanal (Naef and Velluz, 2001; Gancel et al, 2002; Chisholm et al, 2003a,b; Cannon et al, 2015), squalene (Cheong et al, 2011b; Jiang et al, 2011), linoleic acid (Cheong et al, 2011b, 2012; Jiang et al, 2011), heptadecanoic acid (Delort and Jaquier, 2009; Jiang et al, 2011) or neophytadiene (Delort and Jaquier, 2009; Delort et al, 2015) than distillation or cold press extraction, and it fails to extract many monoterpene and sesquiterpene compounds which are characteristic of Citrus EOs (Jiang et al, 2011). Moreover, there are other minority extraction methods that use also organic solvents such as simultaneous distillation and extraction (SDE) (Akakabe et al, 2008; Kerdchoechuen et al, 2010; Sun et al, 2014a), microwave-assisted extraction (MAE) (Sun et al, 2014a; Liu et al, 2015), and ultrasonic-assisted extraction (UAE) (Alissandrakis et al, 2003; Darjazi, 2011b; Liu et al, 2012; Sun et al, 2014a; Zhang et al, 2017).…”
Section: Techniques To Extract Citrus Volatile Compoundsmentioning
confidence: 99%
“…In fact, medium polarity solvents (diethyl ether, dichloromethane or ethyl acetate) extract more polar and higher MW compounds such as hexadecanal (Naef and Velluz, 2001; Gancel et al, 2002; Chisholm et al, 2003a,b; Cannon et al, 2015), squalene (Cheong et al, 2011b; Jiang et al, 2011), linoleic acid (Cheong et al, 2011b, 2012; Jiang et al, 2011), heptadecanoic acid (Delort and Jaquier, 2009; Jiang et al, 2011) or neophytadiene (Delort and Jaquier, 2009; Delort et al, 2015) than distillation or cold press extraction, and it fails to extract many monoterpene and sesquiterpene compounds which are characteristic of Citrus EOs (Jiang et al, 2011). Moreover, there are other minority extraction methods that use also organic solvents such as simultaneous distillation and extraction (SDE) (Akakabe et al, 2008; Kerdchoechuen et al, 2010; Sun et al, 2014a), microwave-assisted extraction (MAE) (Sun et al, 2014a; Liu et al, 2015), and ultrasonic-assisted extraction (UAE) (Alissandrakis et al, 2003; Darjazi, 2011b; Liu et al, 2012; Sun et al, 2014a; Zhang et al, 2017).…”
Section: Techniques To Extract Citrus Volatile Compoundsmentioning
confidence: 99%
“…Alloaromadendrene was reported as the one of main volatile compounds in the leaves of bitter orange (Ahmad et al., 2006 ). Geranyl acetate, which has a floral‐rosy odor (Jirovetz et al., 2006 ), has been found in citrus peels, leaves, and blooms (Darjazi, 2011 ). On the other hand, certain volatile compounds were not found in the citrus peels (O2, O3, O6, T2, T3, and T6), while some volatile compounds, which were contained in the citrus peel, were specific depending on the extraction method (O4, O5, T4, and T5).…”
Section: Resultsmentioning
confidence: 99%
“…Geranyl acetate, which has a floral-rosy odor (Jirovetz et al, 2006), has been found in citrus peels, leaves, and blooms (Darjazi, 2011).…”
Section: The Changes In Volatile Profiles Based On Different Extract ...mentioning
confidence: 99%
“…In studies on flower odorants, solid phase microextraction (SPME) ( Wang et al, 2009 ), dynamic headspace ( Ohashi et al, 2019 ) and solvent extraction ( Darjazi, 2011 ) methods are commonly used to extract volatiles. Gas chromatographer (GC) matched mass spectrometry (MS), olfactory and flame ionization detector (FID) are commonly detection equipment ( Darjazi, 2011 ; Dugo et al, 2011 ; Ohashi et al, 2019 ). Many studies have been performed on the volatiles of citrus flowers, mainly focusing on oranges and mandarin varieties.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been performed on the volatiles of citrus flowers, mainly focusing on oranges and mandarin varieties. Behzad Babazadeh reported that 37 volatiles were detected in ‘Page’ mandarin flowers using GC − MS and GC-FID ( Darjazi, 2011 ). Alissandrakis et al (2003) reported that linalool was the predominant component in orange (51.6%), tangerine (75.2%) and sour orange (80.6%) flowers, and that eucalyptol was the main volatile component in lemon (35.7%).…”
Section: Introductionmentioning
confidence: 99%